2002
DOI: 10.1128/iai.70.12.7145-7148.2002
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Immunological Decline during Long-Term Experimental Infection withMycobacterium avium

Abstract: Terminal loss of immune responsiveness in C57BL/10 mice intranasally infected with Mycobacterium avium was observed in both spleen and lung. It was nonspecific and related to the duration of infection, not the age of the mice. While there was loss of total T cells, the remaining cells were less efficient at gamma interferon production

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The high rate of T‐cell apoptosis was preceded by a high rate of CD4 + and CD8 + T‐cell proliferation in vivo 25 suggesting the possibility of AICD. Both CD4 + and CD8 + T cells were steadily depleted from the spleen 26 and other tissues 27 . Ultimately, even the remaining T cells lost their ability to produce protective IFN‐γ and the mice became moribund, with bacterial numbers exceeding 10 9 /lung.…”
Section: Introductionmentioning
confidence: 99%
“…The high rate of T‐cell apoptosis was preceded by a high rate of CD4 + and CD8 + T‐cell proliferation in vivo 25 suggesting the possibility of AICD. Both CD4 + and CD8 + T cells were steadily depleted from the spleen 26 and other tissues 27 . Ultimately, even the remaining T cells lost their ability to produce protective IFN‐γ and the mice became moribund, with bacterial numbers exceeding 10 9 /lung.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a less virulent strain (M. avium 2447) did not (9). In a different model of infection initiated by exposure to an intratracheal infection, Cheers and colleagues dissected the development of severe anergy associated with pronounced T-cell loss at late stages of M. avium infection (13,14,24). In the latter studies, such T-cell loss was observed at different sites of infection and was explained by the increase in apoptosis of T cells in infected animals (14).…”
mentioning
confidence: 99%